Model Kemitraan dalam Program Pembinaan Kemandirian Narapidana di Lembaga Pemasyarakatan Kelas II A Tanjungpinang - Utari Sunia; Edison Edison; Fitri Kurnianingsih (Policy, Law and Political Research Center, 2022)
This study examines the Partnership Model in the Correctional Inmates Independence Development Program at the Class IIA Tanjungpinang Penitentiary. The problem of this research shows that there is a discrepancy in the implementation of guidance in Government Regulation No. 57 of 1999 regarding cooperation in the implementation of development so that there are still minimal partnerships that exist which then have an impact on product stagnation as the result of the work of the inmates. The purpose of this study was to find out how the partnership model in the inmates' independence development program at the Class IIA Tanjungpinang Penitentiary was effective and optimal in empowering the inmates. The research method used by the researcher is descriptive qualitative method with data collection techniques and tools in the form of documentation, observation, and interviews. In the results of the study, it was found that there was ambiguity in the partnership that had been established because there was no written document that unified and binds the partnering parties. In practice, the coaching program has been carried out according to Standard Operating Procedures, but the lack of program supporting factors is an obstacle to the implementation of self-reliance development. It can be concluded from the partnership model that has been established has not shown effective and optimal results